TRANSFORMASI CITY BRANDING DI JAKARTA MENUJU KOTA KOLABORASI - Aprianto, Happy; Nurhasana, Renny; Badry, Ahmad Ibrahim (ITB AAS Indonesia Surakarta, 2024)
A strong regional and global marketing strategy is needed to create a quality city identity. City branding that has been carried out with the tagline